Empirical Research on Corporate Social Responsibility in the Logistics Company - Činčalová, Simona (International Business Information Management Association-IBIMA, 2018)
This paper deals with Corporate Social Responsibility (CSR) in Logistics Company. Corporate social responsibility (CSR) promotes a vision of business accountability to a wide range of stakeholders, besides shareholders and investors. Key areas of concern are environmental protection and the wellbeing of employees, the community and civil society in general, both now and in the future. Nowadays CSR has become an essential part of big, multinational corporations without which any corporation of a substantial size would face difficulties from various fronts – non-government organizations, governments, public (including existing and potential customers), and even workforce itself. As in any other business, CSR has a positive effect in logistics. The long-term financial success of businesses is increasingly linked to corporate social responsibility and reporting. In August 2017, interviews with warehousemen (as one of key employees) associated with CSR conducted in the selected logistics company in the Czech Republic. According to these talks, recommendations were defined.
Empirický výzkum společenské odpovědnosti firem v logistickém podniku
Keywords: CSR; logistics; warehousemen; CSR; logistika; skladník